The Contribution of Rural Women to Family Economy through Informal Sector Activities - Arsal, Thriwaty; Basri, Muhammad; Tono, Sumartono (KOMUNITAS: INTERNATIONAL JOURNAL OF INDONESIAN SOCIETY AND CULTURE, 2017)
Economic contribution of bakul women (small tradeswomen) was manifested in informal sector activities such as merchants, laborers, homeworkers, and family workers. As well as, rural society activities indicated cooperation between men and women. One job conducted by women in informal sector was bakul. The work is a progress for women regarding work division; however, it is also a challenge, especially for children education in the family. Research location was in Gunungpati Subdistrict, Semarang City. The research was conducted using qualitative approach. Research result shows that bakul women worked in informal sector to fulfill economic need of the family because the income from their husband was insufficient to fulfill daily needs thus they tried to look for additional income.Â Â